The Impact of Economic Growth and Tiered Medical Policy on the Medical Waste Generation: An Empirical Analysis Based on the Environmental Kuznets Curve Model - Ma, Yan; Jia, Linlin; Hou, Yanhong; Wu, Xiaoming (Frontiers in Environmental Science, 2022)
Medical waste has a high environmental risk, economic development and medical policies can affect medical waste generation. Per capita gross domestic product (GDP) is an important indicator to measure the macroeconomic development status, and the tiered medical policy plays an important role in the process of China's medical reform. The study considered the Environmental Kuznets Curve (EKC) of medical waste generation (MWG) in 8 cities in China from 2013 to 2019, using economic indicator (GDP per capita) and policy indicator (tiered medical policy) to reveal the impact of economic development and medical policy on MWG. Furthermore, residents, especially the elderly, are the main consumers of medical resources, and medical institutions are the main places where medical waste is generated. Education level can affect waste management practices. Therefore, the research introduced population size, number of medical institutions, aging degree and education level as control variables. The results confirmed the validity of the N-shaped EKC curve between medical waste and GDP per capita. The amount of medical waste would continue to increase with economic growth, but the growth rate was not fixed. Implementing the tiered medical policy had shown a trend towards reducing medical waste. Population size and aging degree positively affected the generation of medical waste. The number of medical institutions negatively affected the generation of medical waste. The effect of education level on MWG could be ignored. Based on the empirical analysis results, this research put forward relevant policy suggestions in the light of medical waste management practice in China.